Makna Simbol Salib pada Kain Tenun Sekomandi: Suatu Studi Etnografi - Hasibuan, Serepina Yoshika; Larosa, Setiaman (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
The cross is the main symbol often used by Christians and is widely known by non-Christian communities. The cross is usually interpreted as a symbol of the sacrifice of the Lord Jesus to redeem humans from sins. Uniquely, this symbol appears in the traditional cloth of the Kalumpang tribe. This research aims to explore the meaning of these symbols on the Sekomandi woven cloth typical of the Kalumpang people. The method used is a qualitative method with an ethnographic approach. Researchers observed the location, conducted in-depth interviews with several traditional and religious leaders there. The findings obtained are that the meaning of the cross for the people of Kalumpang symbolizes group identity and appreciation for the servants of God who have served in their village. The values ​​raised are sacrifice, appreciation and hope for the prosperity of the village in the future. So, the cross is interpreted more sociologically, historically and economically than Christologically.